THE LEGAL FORCE OF THE PRINCIPLES APPLIED BY COURT OF JUSTICE OF THE EUROPEAN UNION - MILITARU, Ioana Nely (International Journal of Legal and Social Order, 2022)
The Court of Justice of the European Union applies, in addition to the general principles of law, other principles in the cases brought before it, which are used by the Member States and, in particular, by the courts. One category includes fundamental human rights, which are regarded as a variety of general principles. Another category of principles guides the procedure for deciding cases before national courts, namely: the principle of respect for the rights of the defence, the principle of equality, the principle of legal certainty, etc. All have been applied by the Court of Justice of the European Union since the European Communities were founded.